Benefits of Digital Mental Health Care Interventions for Correctional Workers and Other Public Safety Personnel: A Narrative Review - Moghimi, Elnaz; Knyahnytska, Yuliya; Omrani, Mohsen; Nikjoo, Niloofar; Stephenson, Callum; Layzell, Gina; Frederic Simpson, Alexander Ian; Alavi, Nazanin (Frontiers in Psychiatry, 2022)
Chronic exposure to stressors and potentially psychologically traumatic events contributes to the high prevalence of mental health disorders in correctional workers (CWs) and other public safety personnel (PSP). Digital mental health interventions are an accessible and scalable method of improving and maintaining the mental health of this population. The current review explores the benefits of digital mental health interventions for PSP - with a focus on CWs - and how these innovations can address the limitations in in-person mental health care. A systematic literature search of five databases (Medline, PsycInfo, Embase, CINAHL, Google Scholar) was conducted until March 2022. The search yielded 16 publications that focused on digital mental health interventions or care available to CWs and other PSP. The benefits of digital innovations were summarized into five categories which discussed (1) their ability to enhance accessibility and reduce stigma; (2) the efficiency in developing and disseminating evidence-based and structured psychotherapy programs; (3) the flexibility in the degree of therapist engagement; (4) the importance of integrating proactive interventions; and (5) enhancing engagement by developing sector-specific and socially supportive digital programs. Although digital mental health technologies for CWs are still in their infancy, there is strong evidence to support their effectiveness in ameliorating symptoms of mental distress. Future research should consider how ethnicity, gender, culture, sexual orientation, and socioeconomic status can be integrated into these therapies and how the interplay between different stakeholders and organizations can impact the effectiveness of online therapies and programs.